Beyond Mental and Physical Pain: A Non-Reductive Account of Suicide - Ragheb, Aya Aly (AUC Knowledge Fountain, 2021)
What is the stigma behind our understanding of suicide? What causes this stigma? Should suicide only be viewed in relation to physical pain, as medicine often views it, or mental pain, as psychiatry views it? Or is it a more complex phenomenon? Can we think of suicide as a rational act that is, on the one hand, independent of pain, without, on the other hand, reducing it to mental illness? I will argue that if we can, we can give a less reductive account of suicide. In this paper, we shall attempt to give an answer to the above questions while investigating the Stoics’ model of suicide first and their answer to the question, followed by the contemporary debate regarding the permissibility of suicide, then we shall explore Albert Camus’ view on the topic. The views of the Stoics and Camus shall be compared. Then, we shall propose a theory that combines both systems, a classical and a modern model of suicide, to arrive at an answer to later show how the proposed theory answers some of the questions raised by contemporaries.